2013
DOI: 10.5897/ajmr12.1926
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potency of some entomopathogenic bacteria isolated from insect cadavers on Anopheles arabiensis Giles (Order: Dipthera; Family: Culicidae) mosquito larvae in Nigeria

Abstract: The laboratory evaluation of larvicidal activities of some bacteria namely; Pseudomonas aeruginosa, Bacillus polymyxa and and Bacillus subtilis was assessed against the second and fourth instar of Anopheles arabiensis collected from South West Nigeria. Concentrations ranging from 1.3 x 10 7 cfu/mL to 6.5 x 10 7 cfu/mL were tested on the larvae for a period of 48 h. The disparity in the activities was monitored with B. subtilis displaying the highest activity in both the second and fourth instar with LC 50 of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…This genus is the most studied group of bacteria in insect pathology (Boemare and Tailliez 2010) and is commonly recognized as definitive insect pathogens (Stahly et al 2006;Masetti et al 2008). Among Bacillus species, Bacillus subtilis (CQ3) and Bacillus tequilensis (CQ4) have been isolated from many insect species belonging to a variety of different orders at various times (Omoya and Akinyosoye 2011;Sevim et al 2012a). In one study, Omoya and Akinyosoye (2011) isolated and characterized a Bacillus subtilis strain from cockroaches, and indicated that it had a significant effect on Anopheles arabiensis, the main malaria vector.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This genus is the most studied group of bacteria in insect pathology (Boemare and Tailliez 2010) and is commonly recognized as definitive insect pathogens (Stahly et al 2006;Masetti et al 2008). Among Bacillus species, Bacillus subtilis (CQ3) and Bacillus tequilensis (CQ4) have been isolated from many insect species belonging to a variety of different orders at various times (Omoya and Akinyosoye 2011;Sevim et al 2012a). In one study, Omoya and Akinyosoye (2011) isolated and characterized a Bacillus subtilis strain from cockroaches, and indicated that it had a significant effect on Anopheles arabiensis, the main malaria vector.…”
Section: Discussionmentioning
confidence: 98%
“…Among Bacillus species, Bacillus subtilis (CQ3) and Bacillus tequilensis (CQ4) have been isolated from many insect species belonging to a variety of different orders at various times (Omoya and Akinyosoye 2011;Sevim et al 2012a). In one study, Omoya and Akinyosoye (2011) isolated and characterized a Bacillus subtilis strain from cockroaches, and indicated that it had a significant effect on Anopheles arabiensis, the main malaria vector. We also found B. subtilis from C. quadrimaculatus to be an effective pathogen, and had 100 % insecticidal activity on this pest.…”
Section: Discussionmentioning
confidence: 98%
“…Lalithambika et al (2014) reported the efficient biocontrol of the Dengue Vector A. aegypti (Diptera: Culicidae) using an exotoxin derived from P. fluorescens. Omoya and Akinyosoye (2011) and Mostakim et al (2012) reported the larvicidal potency of P. aeruginosa strains on the Anopheles arabiensis (Diptera: Culicidae), the main malaria vector in Nigeria and the olive fruit fly Bactrocera oleae larvae (Diptera: Tephritidae) respectively. Silva et al (2014) reported the larvicidal potency of P. aeruginosa LBI 2A1 derived rhamnolipids against A. aegypti larvae.…”
Section: Insecticidal Activity Of Pseudomonas Derived Biopesticidesmentioning
confidence: 98%
“…It was originally isolated from natural Lepidopteran die-offs in Germany and Japan. Activity of Bt against species of mosquitoes were reported [57]. Bt products have been available since the 1950s.…”
Section: Microbial Insecticidesmentioning
confidence: 99%